Polycentric City Regions in Transformation. The Ruhr Agglomeration in International Perspective. - (:unkn) unknown (Lit, 2019)
Worldwide, cities and regions are affected by structural change and face comprehensive transformation processes, many of which are yet to reveal themselves. In this context, polycentric models for development have been internationally voiced. Polycentric City Regions in Transformation: The Ruhr Agglomeration in International Perspective discusses such models in a comparative manner and, in particular, focuses on the dynamics that shape and challenge cities and regions nowadays. The book compiles contributions from Germany, China, Canada, Portugal, Colombia, USA, Scotland, among others, which were presented in an international conference held at Essen Zollverein in June 2015.
Keywords: Stadtregion; Polyzentralität; Transformation; Agglomeration; Strukturwandel; Regionalentwicklung; Stadtentwicklung